Eudragit (R) EPO based nanoparticle suspension of andrographolide: in vitro and in vivo - Bothiraja, C.; Pawar, Atmaram P.; Shaikh, Karimunnisa S.; Sher, Praveen (Nanoscience and Nanotechnology Letters, 2009)
Characteristic formulation of an isolated active phytoconstituent is of great therapeutic significance. The purpose of this work was to develop Eudragit (R) EPO based nanoparticle suspension of isolated andrographolide in order to increase its solubility and efficacy. Andrographolide was isolated from Andrographis paniculata and Its Nanoparticle suspension was prepared by precipitation technique. The 3(2) factorial design was used to study the effect of Eudragit (R) EPO and Pluronic (R) F-68 on characteristics of nanoparticle suspension. The optimized formulation was subjected to lyophilization. The nanoparticle suspension, lyophilized suspension and the redispersed lyophilized nanoparticle suspension were characterized by drug content, encapsulation efficiency, particle size, electrokinetic properties, DSC, PXRD, FTIR, TEM and in vitro drug release. Optimized batch showed particle size 255 +/- 9 nm with encapsulation efficiency 93.8 +/- 0.67% and zeta potential 29.3 +/- 3.4 mV. There was marked increase in drug dissolution with complete drug release within 10 minutes in nanoparticle suspension and redispersed naoparticle suspension as compared to pure drug. However, lyophilization retarded the drug release. The nanoparticle suspension and redispersed nanoparticle suspension also showed improved hepatoprotectivity as compared to andrographolide against CCl(4)-induced hepatotoxicity in rats. The results were confirmed by histopathological studies on hepatic lesions. Thus particle engineering can be used to improve pharmaceutical properties of phytoconstituents.
Keywords: Andrographolide; Eudragit (R) EPO; Hepatoprotective Activity; Nanoparticle Suspension; Pluronic (R) F-68